Gramsci in Italia, studi e ricerche tra filologia e politica (2018-2021) - Liguori, Guido (International Gramsci Journal, 2023)
This is the Abstract of the Italian-language article by Guido Liguori on the present-day studies of Gramsci in Italy and Gramsci publications there after the 2017 round of conferences.